Bacteriophage-insensitive mutants for high quality Crescenza manufacture - Chirico, Donatella; Gorla, Arianna; Verga, Viola; Pedersen, Per D.; Polgatti, Eliseo; Cava, Antonio; Dal Bello, Fabio (Frontiers in Microbiology, 2014)
Streptococcus thermophilus is a thermophilic lactic acid bacterium used as starter culture for the manufacture of fermented dairy products. For the production of Crescenza and other soft cheeses, Sacco has developed and provides dairies with 3 different defined blends of S. thermophilus strains. Each blend contains 2 different S. thermophilus strains. The strains were selected based on their unique technological properties as well as different phage profiles. Analysis of 133 whey samples collected in 2009-2010 from Italian dairies showed a high prevalence (about 50%) of bacteriophage attacks on the blend ST020. More specifically, the strain S. thermophilus ST1A was found to be the preferred target of the bacteriophages. A bacteriophage insensitive mutant (BIM5) of the phage-sensitive strain ST1A was successfully developed and used to substitute strain ST1A in the Crescenza starter culture ST020. The strain BIM5 showed identical technological and industrial traits as those of the phage-sensitive strain ST1A. The improved resistance of the modified Crescenza starter culture ST020R was confirmed at Italian dairies, and its effectiveness monitored on 122 whey samples collected in 2011-2012. Compared to the previous values (2009-2010), the use of the phage-hardened blend ST020R allowed reducing of frequency of phage attacks from about 50 to less than 5% of the whey samples investigated.